"Rumours are Circulating Here at Court…" News from European Courts in Polish-Language Handwritten Newspapers, as Reflected in the Subscriptions of Elżbieta Sieniawska (née Lubomirska), Castellan of Kraków (d. 1729) - Łękawska, Monika (Sensus Historiae, 2026)
The article examines Polish‑language manuscript newspapers subscribed by Elżbieta Sieniawska (d. 1729) in order to reconstruct contemporary images of European courts at the turn of the seventeenth and eighteenth centuries. Local editors and information agents collected and translated material from foreign gazettes, thereby constructing images of foreign courts that were often simplified, stereotyped or overtly propagandistic. These portrayals nonetheless exerted a tangible influence on the political awareness, cultural tastes and imitative aspirations of the noble readership. In this sense, manuscript press emerges in the article as a crucial medium - a kind of ‘fourth estate’ - in mediating the Polish public’s perception of European political realities and the web of relations between the ruling houses.